Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18168542
|View full text |Cite
|
Sign up to set email alerts
|

The Patterns and Impact of Off-Working Hours, Weekends and Seasonal Admissions of Patients with Major Trauma in a Level 1 Trauma Center

Abstract: Background: The trauma incidence follows specific patterns in different societies and is expected to increase over the weekend and nighttime. We aimed to explore and analyze the incidence, pattern, and severity of trauma at different times (working hours vs. out off-working hours, weekdays vs. weekends and season). Methods: A retrospective analysis was conducted at a level 1 trauma facility in Qatar. All injured patients admitted between June 2017 and May 2018 were included. The data were analyzed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…25,26 In contrast, some studies have found no significant seasonal variation in facial trauma admissions. 27,28 Given that much of the seasonal variation in facial fractures is likely due to sociocultural or weather-related factors, we sought to further investigate and quantify these seasonal trends amongst the adult population presenting to a Level 1 Trauma center in the Northeast United States. This location has a mean annual temperature of 53°F.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 In contrast, some studies have found no significant seasonal variation in facial trauma admissions. 27,28 Given that much of the seasonal variation in facial fractures is likely due to sociocultural or weather-related factors, we sought to further investigate and quantify these seasonal trends amongst the adult population presenting to a Level 1 Trauma center in the Northeast United States. This location has a mean annual temperature of 53°F.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In contrast, some studies have found no significant seasonal variation in facial trauma admissions. 27,28…”
Section: Introductionmentioning
confidence: 99%